HUKUM WARIS ISLAM DI INDONESIA (ANTARA KOMPILASI HUKUM ISLAM DAN PRAKTIK SOSIAL) - Aji Nugroho, Renal; Indiarto Hutomo, Ferdinan; Suwarno Putro, Roy; Anaba, D Bayu; Dwi Wardian Ningrum, Yessy; Mul Erowati, Eti (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This study examines the gap between the provisions of the Compilation of Islamic Law (KHI) and social practices in Indonesia concerning inheritance distribution. It highlights the influence of cultural traditions, economic disparities, and varied religious understandings on the application of Islamic inheritance law. Using a qualitative approach with a socio-legal perspective, data were gathered from legal documents and relevant literature. The findings indicate that KHI often requires contextual adjustments to local conditions. This research emphasizes the need for inclusive legal education and the harmonization of formal Islamic law with social practices to ensure justice and family harmony.